Purpose and Intent: Seeking A More Consistent Approach to Stream of Commerce Personal Jurisdiction - Shane Yeargan (Washington University Law Review, 2012)
The stream of commerce theory of personal jurisdiction has existed in a state of confusion and uncertainty for more than a quarter of a century. Much of this uncertainty stems from the fact that the Supreme Court has not been able to produce a majority opinion outlining the appropriate scope of jurisdiction under the stream of commerce theory. In 1987, the Court’s plurality opinions in Asahi Metal Industry Co. v. Superior Court of California developed two competing versions of the stream of commerce theory, which left lower courts to guess at the appropriate standard for the theory. In 2011, many hoped that the Court would resolve this uncertainty when it took up J. McIntyre Machinery, Ltd. v. Nicastro. These hopes were disappointed by another plurality opinion. Although the majority of justices appear to favor Justice O’Connor’s approach to stream of commerce theory, the proper scope of the standard is still unclear. This Note argues that the jurisprudence surrounding J. McIntyre and Asahi largely conflates the standard for stream of commerce personal jurisdiction with the types of proof sufficient to support such jurisdiction. Further, this Note contends that the focus when determining personal jurisdiction in a stream of commerce context should be on the intent of the defendant regarding the forum, which serves as a means of determining whether there is purposeful availment that creates the necessary minimum contacts between the forum and defendant. A series of concrete rules are proposed to give form to this principle.
Keywords: Asahi Metal Industry Co. v. Superior Court of California; J. McIntyre Machinery Ltd. v. Nicastro; stream of commerce; personal jurisdiction; supreme court; civil procedure; purposeful availment